2018
DOI: 10.1051/matecconf/201815004008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starch sizes particle as binder on short pineapple leaf fiber composite mechanical properties

Abstract: Abstract. Pineapple leaf fiber (PLF) is one of the natural fibers that abundantly can be found in Malaysia, but the usage of the pineapple plant is limited only on their fruit and the other parts to be a waste. In this study, PLF is used as the reinforcement material and starch (SH) used as the matrix or binder. Both materials were combined with several compositions ratio (weight percentage) of PLF/SH composites which are 50PLF/50SH, 60PLF/40SH and 70PLF/30SH. Before undergo the fabrication process, the fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition, micromechanical model is used to classify heterogeneous materials like composite [23,24]. Generally, many parameters influence the micromechanical properties of the composite such as fibre and matrix properties, fibre and matrix loading, size of the composite, fibre and matrix sources, interfacial adhesion between the fibre and matrix and orientation of the composite [25][26][27][28][29][30][31]. The most frequently used micromechanical models are rule of mixtures (ROM), rule of hybrid mixtures (ROHM), Halpin-Tsai equation and Tsai-Pagano equation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, micromechanical model is used to classify heterogeneous materials like composite [23,24]. Generally, many parameters influence the micromechanical properties of the composite such as fibre and matrix properties, fibre and matrix loading, size of the composite, fibre and matrix sources, interfacial adhesion between the fibre and matrix and orientation of the composite [25][26][27][28][29][30][31]. The most frequently used micromechanical models are rule of mixtures (ROM), rule of hybrid mixtures (ROHM), Halpin-Tsai equation and Tsai-Pagano equation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, past research has shown that the utilization of a fine fiber geometrical structure is only advantageous to the composite if adequate binder is applied. 112 According to Das et al 113 when forming a bond between fibers, the binder plays a crucial function in generating a vast connection of fiber network, which contributes to the transmission of load between fiber particles in the composite. Consistent with a previous study, their findings indicated that fibers with a fine geometrical structure that lacked a binder suffered a significant disadvantage due to their inability to undergo particle bonding, resulting in a reduction of load distribution properties throughout the composite panel.…”
Section: The Influence Of Fiber Physico-chemical Propertiesmentioning
confidence: 99%
“…It indicates the uncertainty in the measured ap proximation values. In a recent study, the error bar was an informative tool to show the goodness of fit or dispersion of the data set [55,56]. In detail, statistical testing such as hypothesis testing, confidence interval and ttest should be performed to draw the final conclusion.…”
Section: Materials Selection Based On Performance Of Mechanical Propermentioning
confidence: 99%